1981
DOI: 10.5558/tfc57017-1
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Analysis and DRIS as a Guide to Fertilizer Amendments in Poplar Plantations

Abstract: The use of foliar analysis in conjunction with the Diagnostic and Recommendation lntegrated System (DRIS) of Beaufils is demonstrated for the poplar clone D38 (Populus deltoides Marsh.) to guide fertilizer amendments and monitor subsequent tree growth by use of field and greenhouse standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 3 publications
2
8
0
2
Order By: Relevance
“…Preliminary studies have identified nutritional status as the major parameter determining the productivity of various Populus species, which is consistent with findings in other areas van den Driessche 2002, 2005;Leech and Kim 1981;McLennan 1996;van den Driessche 1999;van den Driessche et al 2003). However, despite the important economic implications, the main factors involved in the poor growth of these plantations have not yet been established.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Preliminary studies have identified nutritional status as the major parameter determining the productivity of various Populus species, which is consistent with findings in other areas van den Driessche 2002, 2005;Leech and Kim 1981;McLennan 1996;van den Driessche 1999;van den Driessche et al 2003). However, despite the important economic implications, the main factors involved in the poor growth of these plantations have not yet been established.…”
Section: Introductionsupporting
confidence: 63%
“…Foliar nutrient balance was initially analyzed by DRIS indices calculated for N, P, K, Ca and Mg from norms developed by Leech and Kim (1981). However, preliminary results showed that micronutrients were the most influential variables, and the resulting DRIS indices were not encouraging.…”
Section: Sampling and Analysis Of Soils And Leavesmentioning
confidence: 99%
“…This indicates that most of these traits are under strong environmental control in hybrid poplar clones of different parentages. Variation in foliage and leaf litter nutrient concentrations along site fertility gradients often reflect changes in nutritional or physiological status [65,66], potential nutrient limitations [67], but also trends in nutrient cycling strategies [11,39]. Our results showed that resorption proficiency (i.e.…”
Section: Discussionmentioning
confidence: 54%
“…8), reflecting the effect of NH 4 NO 3 in accentuating the adverse effect of pH (Gupta and MacLoed, 1981). Most studies place critical P concentrations of different hybrid poplar varieties above or around 0.25% (Leech and Kim, 1981;Hansen, 1994;McLennan, 1996). Leaf P concentrations of unfertilized trees in this study were already below 0.20%, and the high N level reduced P concentrations by about 0.195-0.185% (Fig.…”
Section: Discussionmentioning
confidence: 96%